Pendampingan Peningkatan Ketrampilan Sumberdaya Karyawan Pabrik Tahu Pinti Kayu di Kec. KPGD Kab. Solok Selatan - Sari, Nia Komala; Hartini, Hartini; Apriyanti, Eka; Adriani, Adriani (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
The aim of this community service activity is to provide knowledge to the community regarding the human resource management system in developing the tofu factory business. The partner of this activity is Mr. Haminuddin's tofu making business which is located in Nagari Pakan Rabaa Timur, precisely Jl, Ladang Konsi, Pinti Kayu District. . KPGD District. South Solok. This activity was carried out from 1-30 May 2023. The methods applied were interviews, observation, training and mentoring. The results of this activity found information that the HR management system at the tofu factory uses a family system in recruiting and nurturing employees, the production process and tools used in making tofu still use simple methods, analyzing capital, and marketing the production results using a mouth-to-mouth system. to mouth. From this activity, the income generated by the tofu factory business per day can increase. The income earned is enough to support the business owner's family and pay employee wages